Incomplete Excisions of Melanocytic Lesions: Rates and Risk Factors - Sofia Berglund; Eva Johansson Backman; Zahra Baldawi; Linda Horn; Rebecca Arbin Borsiin; Michelle Marjanovic; Thea Christoffersson; Martin Gillstedt; John Paoli (Medical Journals Sweden, 2021)
Incomplete excisions of melanocytic lesions occur despite the intention of complete removal. The aim of this study was to determine the incomplete excision rates for benign and malignant melanocytic lesions and the associated risk factors. Demographic, clinical, and histopathological data possibly associated with incomplete excision were collected from 2,782 consecutive excisions between 2014 and 2015. Of these, 269 melanocytic lesions (9.7%) were incompletely excised. Multivariate analysis revealed the following risk factors for significantly higher incomplete excision rates: lesions located in the head and neck area (odds ratio (OR) 3.95, 95% confidence interval (95% CI) 2.35-6.65), surgery performed by general practitioners (OR 3.01, 95% CI 2.16-4.19), the use of a punch excision technique (OR 2.83, 95% CI 1.96-4.08), and excision of non-dysplastic naevi (OR 1.58, 95% CI 1.11-2.23). In conclusion, more caution should be taken when excising melanocytic lesions in the head and neck area, general practitioners require more surgical training, and punch excisions of melanocytic lesions should be avoided.